Knowledge of the Ovulatory Period and Associated Factors Among Reproductive Women in Ethiopia: A Population-Based Study Using the 2016 Ethiopian Demographic Health Survey - Getahun MB; Nigatu AG (Dove Medical Press, 2020)
Melaku Bimerew Getahun, Addisu Getie Nigatu Department of Nursing, College of Health Sciences, Woldia University, Woldia, EthiopiaCorrespondence: Melaku Bimerew Getahun Tel +251923065826Email mebiget@gmail.comPurpose: In the era of increasing health risks, refusals, discontinuations, and with high unmet needs for modern contraception, assessing knowledge of the ovulation period and identifying its associated factors among reproductive women are crucial to recommend natural family planning methods as an option. So, the aim of this Demographic Health Survey analysis was to assess knowledge of the ovulation period and its associated factors among reproductive women in Ethiopia.Methods: A secondary data analysis using the 2016 Ethiopian Demographic Health Survey was done by applying the principles of cross-sectional study design. Descriptive statistics and logistic regressions were used. Odds ratio with 95% confidence interval was used to interpret associations, and a significant association was declared at a p-value of < 0.05.Results: A total of 15,683 women aged from 15 to 49 years were included in this analysis. Of them, only 3,699 (23.6%) were found to be knowledgeable about a woman’s ovulation period. Women with age > 39 years (AOR=1.77; 95% CI=1.52, 2.06), being urban resident (AOR=1.93; 955 CI=1.76, 2.12), having higher educational status (AOR=4.39; 95% CI=3.77, 5.11), getting family planning counselling within the last 12 months (AOR=1.33; 955 CI=1.20, 1.48), use of family planning (AOR=1.23; 95% CI=1.11, 1.37), being pregnant (AOR=1.22; 95% CI=1.03, 1.46), living with husbands (AOR=1.19; 95% CI=1.08, 1.31), and having menstruation within the last 6 months (AOR=1.30; 95% CI=1.18, 1.42) were factors associated with increased knowledge of the ovulation period among reproductive women.Conclusion: Knowledge of the ovulation period among reproductive women in Ethiopia was low. Factors significantly associated with knowledge of the ovulation period were identified, and recommendations were forwarded accordingly.Keywords: knowledge, ovulation period, reproductive women, Ethiopia